ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI UNTUK BERKARIER MENJADI AKUNTAN PUBLIK - RINA KOMALA; KHAIRUNNISA KHAIRUNNISA; STEVANY HANALYNA DETHAN (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to determine: (1) the effect of gender on the Interests Accounting Students for a career Become a Public Accountant, (2) the impact of Choice Financial to interest Accounting Students for a career Become a Public Accountant, (3) the influence Consideration Job Market on Interest Student Accounting for career become a Public Accountant. This research was causal comparative. The sample in this study were students of Accounting Department Faculty of Economics, University of Bumigora class of 2019 until to class of 2021 as many as 80 people. The sampling technique with quota sampling. The data collection technique using a questionnaire (questionnaire). Analysis prerequisite test including normality test, linearity test, test multicollinearity, and heteroscedasticity test. Data analysis technique used is multiple regression analysis using SPSS version 21. The conclusion that can be obtained from this study were (1) There is no effect of gender on the career interest Accounting Students to Become a Public Accountant. (2) There is a significant influence on the Choice Interests Financial Accounting Students to Become a Public Accountant career. (3) There is a significant influence on the Labour Market Considerations in Accounting Student Interests for a career Become a Public Accountant.